DAMPAK ALIH FUNGSI LAHAN PERTANIAN TERHADAP PENDAPATAN PETANI DI DESA SOLOG KECAMATAN LOLAK KABUPATEN BOLAANG MONGONDOW (The Impact of Agricultural Land Conversion on Farmers’ Income in Solog Village Lolak Sub District Bolaang Mongondow Regency) - Teresa Regina Rosa Nangoi; Esry O. H. Laoh; Jenny Baroleh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to determine and describe the impact of agricultural conversion on farmers incomes is Solog Village, Lolak Sub District, Bolaang Mongondow Regency. This research was conducted from May 2021 to July 2021. The data collected is primary data obtained from direct interviews with farmers who own agricultural land using a questionnaire. Sampling by purposive sampling, namely from the populations of farmers affected by land conversion, a total of 35 farmers, samples taken as many as 15 respondents.The research result showed that, the impact of the conversion of agricultural land on the income of farmers in Solog Village, Lolak Sub District, Bolaang Mongondow Regency was positive impacts after land conversion such as the opening of new jobs, new business opportunities such as traders (selling near industrial factories) and the proceeds from land sales repairing houses and buying new houses.Â Negative impact after land conversion was farmersâ€™ income decreases from farming (rice and corn), reduced food production (rice), lack of agricultural land because it has been converted. Formerly farmers who owned the land are now sharecroppers (leasing land). Some of the proceeds from the sale of land are not used as business capital but are used for other purposes such as daily living expenses, so that the monthly income stops.